Analisis Penggunaan APD Terhadap Risiko Kesehatan Petani Penyemprot Pestisida - Amelia Apriyuni; Nurfaizah Hasibuan; Raisa Shabrina Batu Bara; Sri Hajijah Purba (Lembaga Pengembangan Kinerja Dosen, 2024)
Personal protective equipment is a tool used to protect part or all of the body from existing risks. Work related to pesticides can be said to be one of the jobs that has a high level of risk of danger. Personal protective equipment for farmers related to the use of pesticides must be considered because it is one of the preventive and control measures for the risks that farmers will receive. Farmers who do not use personal protective equipment will experience a decline in their health status and work productivity. Farmers who spray pesticides are at risk of experiencing various health problems, Acute Poisoning Symptoms such as dizziness, nausea, vomiting and headaches. Farmers who spray pesticides are at high risk of experiencing various health problems due to exposure to dangerous chemicals. Symptoms such as skin and eye irritation, as well as respiratory problems, Chronic effects Diseases that develop over time, such as endocrine disorders, organ damage, cancer, and reproductive problems. Long-term health problems such as nervous system disorders, respiratory problems, reproductive disorders, and increased risk of cancer. Eye Irritation Direct contact with pesticides can cause skin and eye irritation. The personal protective equipment that can be used includes gloves, masks, safety glasses, long-sleeved clothes and shoes. The method used in writing this journal uses a literature review approach. The sources used in this literature review come from journals obtained from Google Schoolar.